Interhospital variation in the RATPAC Trial (Randomised Assessment of Treatment using Panel Assay of Cardiac markers). Issue 3 (26th May 2011) - Bradburn, Mike; Goodacre, Steve W; Fitzgerald, Patrick; Coats, Tim; Gray, Alasdair; Hassan, Taj; Humphrey, Julian; Kendall, Jason; Smith, Jason; Collinson, Paul; ,
Abstract : Background: The RATPAC trial showed that using a point-of-care panel of CK-MB(mass), myoglobin and troponin at baseline and 90 min increased the proportion of patients successfully discharged home, leading to reduced median length of initial hospital stay. However, it did not change mean hospital stay and may have increased mean costs per patient. The aim of this study was to explore variation in outcome and costs between participating hospitals. Methods: RATPAC was a pragmatic multicentre randomised controlled trial (N=2243) and economic analysis comparing diagnostic assessment using the panel to standard care for patients with acute chest pain due to suspected myocardial infarction at six hospitals. The difference in the proportion of patients successfully discharged (primary outcome) and mean costs per patient between the participating hospitals was compared. Results: Point-of-care assessment led to a higher proportion of successful discharges in four hospitals, a lower proportion in one and was equivocal in another. The OR (95% CI) for the primary outcome varied from 0.12 (0.01 to 1.03) to 11.07 (6.23 to 19.66) with significant heterogeneity between the centres (p<0.001). The mean cost per patient for the intervention group ranged from being £214.49 less than the control group (−132.56 to 657.10) to £646.57 more expensive (73.12 to 1612.71), with weak evidence of heterogeneity between the centres (p=0.0803). Conclusion: The effect of point-of-care panel assessment on successful discharge and costs per patient varied markedly between hospitals and may depend on local protocols, staff practices and available facilities.